Relationship of active and passive smokers to the incidence of pulmonary tuberculosis - Hasanudin, Innayah Salsadilah; Watung, Grace I.V; Darmin, Darmin (Omni Health Journal, 2025)
Background: Tuberculosis is an infectious disease caused by the Mycobacterium Tuberculosis germ. Through these germs, it then spreads from tuberculosis sufferers through the air. Smoking is one of the things that increases the risk of pulmonary tuberculosis. Objective: The purpose of this study was to analyze the relationship between active smokers and passive smokers with the incidence of tuberculosis. Methods: This research method uses a type of analytical research using a cross sectional approach where the sample used is 52 respondents. Results: Based on the results of the chi-square test, it was found that there is a relationship between active smokers and passive smokers with the incidence of Tuberculosis. Conclusion: Based on the results of the analysis, it can be concluded that there is a relationship between active smokers and passive smokers.